2014
DOI: 10.1016/j.sjbs.2013.04.009
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis and in vitro antioxidant functions of protein hydrolysate from backbones of Rastrelliger kanagurta by proteolytic enzymes

Abstract: Every year, a huge quantity of fishery wastes and by-products are generated by fish processing industries. These wastes are either underutilized to produce low market value products or dumped leading to environmental issues. Complete utilization of fishery wastes for recovering value added products would be beneficial to the society and individual. The fish protein hydrolysates and derived peptides of fishery resources are widely used as nutritional supplements, functional ingredients, and flavor enhancers in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
24
1
4

Year Published

2015
2015
2023
2023

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 53 publications
(30 citation statements)
references
References 45 publications
1
24
1
4
Order By: Relevance
“…Reactive oxygen species were major byproducts of oxidative metabolism in the mammalian system, including superoxide anion radicals (O 2 − ) and hydrogen peroxide (H 2 O 2 ), and they can easily react with other substances owing to their active character in the body . It has been reported that the transition metal ion‐dependent OH .…”
Section: Discussionmentioning
confidence: 99%
“…Reactive oxygen species were major byproducts of oxidative metabolism in the mammalian system, including superoxide anion radicals (O 2 − ) and hydrogen peroxide (H 2 O 2 ), and they can easily react with other substances owing to their active character in the body . It has been reported that the transition metal ion‐dependent OH .…”
Section: Discussionmentioning
confidence: 99%
“…Mackerel ( Pneumatophorus japonicus ) is a kind of pelagic fish which has the characteristics of low economic and high productivity, and how to best utilize these positive characteristics of mackerel needs to be addressed. In recent years, there have been many researches on the processing and utilization of mackerel; for example, Donnelly et al [ 8 ] found the cost and benefits of traceability system implementation both electronically and practically in a mackerel supply chain between Japan and Norway; in addition, the research of lipid oxidation and fishy odor development in protein hydrolysates from the muscle of Indian mackerel was reported [ 9 ]; Ferraro et al [ 10 ] also discussed the mackerel canning residues; and Sheriff et al [ 11 ] investigated the hydrolysate from backbones of Indian mackerel, revealing that the hydrolysate contained potent antioxidants and exhibited significant reducing power, free radical scavenging activity, and lipid peroxidation inhibition.…”
Section: Introductionmentioning
confidence: 99%
“…were observed, it was recorded that these values were below the limit value (5 mg M DA eq./kg) accord ing to Schormüller (1969). On the other hand, the TBA Rs value of FA group which was produced with formic acid was significantly higher than the fermented silages.…”
Section: Chemical Assessment Of Fish Silagesmentioning
confidence: 90%
“…The highest DPPH inhibit ion rates were detected at AC and GL groups (P<0.05), but there were no significant differences observed in other groups (P>0.05). Sheriff, Sundaram, Ramamoorthy, & Ponnusamy, (2014) reported that the radical scavenging ability of pepsin and papain derived protein hydrolysates of Indian mackerel (Rastrelliger kanagurta) was found to be a maximu m of 46% and 36%, respectively. Samar, El-Kalyoubi, Khalaf, & ElRazik (2013) recorded that the radical scavenging activity of chitosan samples extracted fro m shrimp wastes using microwave technique were in rage of 16.14%-32.76% (appro ximately 23.68%) at same concentrations.…”
Section: Antioxidant Properties Of Spray-dried Fish Silagesmentioning
confidence: 99%